RESEÑA de : González de León, Fernando. The Road to Rocroi : class, culture andcommand in the Spanish Army of Flanders : 1567-1659. Leiden; Boston : Brill, 2009 - Valladares, Rafael (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2010)
-